2006
DOI: 10.1002/ijc.21884
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori IgA and IgG antibodies, serum pepsinogen I and the risk of gastric cancer: Changes in the risk with extended follow‐up period

Abstract: The prediction of Helicobacter pylori antibodies immunoglobulin A (IgA) and immunoglobulin G (IgG) and serum pepsinogen I (PG I) on gastric cancer occurrence was studied in a nested case-control study, based on 225 incident cancer cases and 435 matched controls from a Finnish cohort followed from 1966-1991. The odds ratio of noncardia gastric cancer between infected and noninfected persons was 3.12 (95% confidence interval (CI) 5 1.97-4.95) for elevated IgA and 2.88 (CI: 1.63-5.07) for elevated IgG antibodies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…8 The increased risk of stomach cancer suggests that local gastrointestinal effects associated with PID, such as the decreased production of gastric IgA and hydrochloric acid, may facilitate Helicobacter pylori colonization and gastric inflammation and promote carcinogenesis. Although there is mixed support for such a pathogenic mechanism, [32][33][34][35] and the role for cofactors such as alterations in the p53 gene are yet to be clarified, 36 these data support the regular use of diagnostic tests and treatment of H pylori infection in adults with PID, together with endoscopic follow-up of those with premalignant gastric lesions. 37 We observed a large excess risk for thymoma on the basis of 2 cases occurring in patients with CVID.…”
Section: Discussionmentioning
confidence: 99%
“…8 The increased risk of stomach cancer suggests that local gastrointestinal effects associated with PID, such as the decreased production of gastric IgA and hydrochloric acid, may facilitate Helicobacter pylori colonization and gastric inflammation and promote carcinogenesis. Although there is mixed support for such a pathogenic mechanism, [32][33][34][35] and the role for cofactors such as alterations in the p53 gene are yet to be clarified, 36 these data support the regular use of diagnostic tests and treatment of H pylori infection in adults with PID, together with endoscopic follow-up of those with premalignant gastric lesions. 37 We observed a large excess risk for thymoma on the basis of 2 cases occurring in patients with CVID.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated 21,178 endoscopies, of which 13,789 were effectively done (65%): 125 cancers were diagnosed, 80% of them at an early stage [138]. Several case-control studies comparing gastric cancer patients with healthy controls, including a range of 84 to 511 cases per study, found statistically significant odds ratios (ORs) for cancer, ranging from 2.24-12.0 for a PGI level <50 ng/mL to an OR of 2.78-10.92 for a PGI/PGII ratio <3 [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155].…”
Section: Biopsy Samplingmentioning
confidence: 99%
“…The evidence supporting this lack of association, however, is based on contradictory findings (Dawsey et al, 2002;Huang et al, 1998Huang et al, , 2003. Studies from Western countries support a negative association between H. pylori infection and cardia cancer (Enroth et al, 2002;Brenner et al, 2004;Kato et al, 2004;Nomura et al, 2005;Shin et al, 2005;Kamangar et al, 2006;Knekt et al, 2006), whereas there is a trend towards positive association in studies from Eastern Asia (Kato et al, 2004;Shin et al, 2005;Yang et al, 2006;Kamangar et al, 2007;Suzuki et al, 2007).…”
Section: Introductionmentioning
confidence: 99%